2015
DOI: 10.1063/1.4917562
|View full text |Cite
|
Sign up to set email alerts
|

Vertical organic transistors withstanding high voltage bias

Abstract: Vertical organic transistors withstanding high voltage bias were realized with an insulating silicon monoxide layer obliquely deposited on both the surface of the base electrode and sidewalls of the vertically oriented cylindrical nanopores. No noticeable insulating layer can be observed on the emitter electrode at the bottom of the cylindrical nanopores. The leakage current between the electrodes was suppressed and an operating voltage as high as 15 V was obtained. An on/off current ratio of 103–104 and an ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…However, porous base electrodes in SCLVTs need to be filled with OSCs, which is a limiting factor for the fabrication technology. 40,61,62 Dollinger et al presented an in situ method for passivating the oxide film of the base electrode by wet electrochemical anodization. It has been demonstrated that such an anodization process is not affecting the C 60 active layer.…”
Section: Overview Of Device Structure and Working Principlementioning
confidence: 99%
“…However, porous base electrodes in SCLVTs need to be filled with OSCs, which is a limiting factor for the fabrication technology. 40,61,62 Dollinger et al presented an in situ method for passivating the oxide film of the base electrode by wet electrochemical anodization. It has been demonstrated that such an anodization process is not affecting the C 60 active layer.…”
Section: Overview Of Device Structure and Working Principlementioning
confidence: 99%
“…The observed J DS was extremely high compared with those of other vertical-type organic transistors. [16][17][18][19][20][21][22][23][24][25][26] The gate current density (J G ) also increased with increasing V DS ; however, the observed J G was three orders of magnitude lower than J DS . Carriers cannot be injected in a gate electrode with increasing positive gate voltage unless the gate voltage exceeds the breakdown voltage.…”
mentioning
confidence: 99%
“…Several groups have reported vertical-type organic transistors such as polymer grid transistors, organic a Email: fukagawa.h-fe@nhk.or.jp b Present address: Tokyo University of Science, Suwa, 5000-1 Toyohira, Chino-city, Nagano, 391-0292, Japan c Present address: Tohoku University, 6-6-05 Aramaki Aza Aoba, Aoba-ku, Sendai, 980-8579, Japan d Present address: Yamagata University, Research Center for Organic Electronics, 4-3-16 Jonan, Yonezawa, Yamagata 992-8510, Japan static induction transistors (SITs), metal-base organic transistors (MBOTs), space-charge-limited transistors (SCLTs), patterned electrode vertical organic field effect transistor (PE-VOFET) and permeable-base transistor (PMBT) to realize a short channel. [15][16][17][18][19][20][21][22][23][24][25][26] However, the relationship between the crystalline axis of the organic film and the carrier transport direction has not been examined for vertical-type organic transistors. If the planar molecules are oriented with the molecular plane parallel to the substrate in a vertical-type organic transistor, the carrier transport direction can easily be aligned with the π-π stacking direction of the organic film.…”
mentioning
confidence: 99%
See 1 more Smart Citation